2019
DOI: 10.1080/10400419.2019.1577674
|View full text |Cite
|
Sign up to set email alerts
|

Autonomy as Core of Creativity and Compliance: Moderated Moderation Model of Maternal Parenting Behaviors

Abstract: Autonomy is one of the core motivators of children's creativity and (non)compliance. But it is less known how children's (non)compliance links to later creative potential and how maternal parenting behaviors contribute to those links. This article, as part of a longitudinal study, tested whether preschoolers' committed compliance and self-assertion related to their potential for motor creativity and how maternal autonomy-supporting and relatedness-supporting behaviors predicted those relations. Eighty-two Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…In literature, it has been shown that creative children have certain positive personality traits such as autonomy (Wang & Dong, 2019), openness to new experiences (Tan et al, 2016), willingness to take risks (Zhang & Sternberg, 2011), being un-conformative (Kim & Park, 2020). These traits fall in line with the general emphasis of good parenting (Sternberg, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In literature, it has been shown that creative children have certain positive personality traits such as autonomy (Wang & Dong, 2019), openness to new experiences (Tan et al, 2016), willingness to take risks (Zhang & Sternberg, 2011), being un-conformative (Kim & Park, 2020). These traits fall in line with the general emphasis of good parenting (Sternberg, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Children with low levels of self-control would fit well with autonomous socialization goals. This is because the characteristics that these children commonly exhibit in toddlerhood, such as assertiveness (e.g., negotiation and saying "no" to parental requests; Wang & Dong, 2019) and the ability to defy (Dix et al, 2007), indicate their expressions of the need for autonomy, such that there is a match between parental expectations for child autonomy and these children's characteristics. In contrast, autonomous socialization goals may be mismatched with children who have high levels of compliance and/or inhibitory control and may link to poorer social adjustment as these children may show too much self-restraint, creating the dissonance between parental expectations and children's actual styles of behaving.…”
Section: Individual Differences In Fit With Environmentmentioning
confidence: 99%
“…Garren (1997) menjabarkan bahwa pola pengasuhan yang mengedepankan sikap-sikap kreatif, seperti peduli, mendukung, dan toleran kepada anak-anaknya serta mendukung kebebasan berpikir dan sikap kemandirian akan dapat menumbuhkan kreativitas pada anak. Begitupula dengan Wang & Dong (2019) yang menemukan bahwa pola perilaku ibu yang mendukung otonomi anak akan dapat memperkuat hubungan antara ketegasan diri (self-assertion) dan potensi kreatif anak.…”
Section: Iklim Hubungan Dan Perilaku Orang Tua Dalam Keluargaunclassified